K fenoménu ruského samozvanectví - Šalanda, Bohuslav (Univerzita Pardubice, 2001)
This paper is a study of the phenomenon of self-appointed Czars, which is closely related to Russian political and historical traditions. In Russia, unique traditions of government, specific because of their quotable history, as well as different utopias and ideals (as for example about a returning Czar-liberator) have existed. These are, in fact, particular symbols of power that were also present in peasant uprisings of the Cossacks (led by Ivan Bolotnikov, Stenka Razin, Jemeljan Pugatshov and other lesser-known historical figures). The phenomenon of self-appointed Czars cannot be understood as Russian only; however, it hasn't been so frequent or has played such an important role in history of other states as it has Russia. The roots of this phenomenon haven't yet been satisfactorily explained. On the social level, the Czar's self-appointment is one of the established forms of antifeudal protest; on the political level, it represents a fight for power. Its religious asperct must also be emphasized, since self-appointment is related to the specific understanding of the Czar's power as a sacral one. The rise of the self-appointed Czars, then, marks the beginning of the process of the sacralizing the emperor. We must add that the self-appointed Czars did not take on only the names of the earlier Czars but also those of saints. There were several waves of Czar self-appointment in Russia history, as represented by Dimitri (died in 1591) and Peter III. This phenomenon also constitutes a specific variation of doubles, since the self-appointed Czar stands in for one who is on the highest level of the political and spiritual power. This double then acts as a deputy for God, for Jesus Christ, for the emperor, etc., a role connected to paternalism and step-fatherhood. The behavior of the self-appointed Czar also contains strong elements of carnival behavior and is, thus, related to fictive emperors in folk rituals and customs. Part of the paper focuses on a self-appointed Czar from Montenegro, the adventure Stepan Maly, who ruled ther successfully between 1767-1773, pretending to be the Russian Czar Petr III. (the real Petr III. was removed from power and executed in 1762 by order of his wife, Catherine II). The following is part of a larger research project about the reception of authority and power, from a trans-cultural point of view.
Keywords: Rusko; dějiny; politika; samozvanectví